Peran Dan Kontribusi Perbankan Syariah Dalam Perekonomian Indonesia: Tinjauan Histori - Aisyah, Aisyah; Ansori, Miswan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Islamic banking has developed into an important part of the world's financial system, especially in Indonesia, which is one of the most populous Muslim countries in the world.. The existence and role of banking in Indonesia, both for society and for large, medium, and small industries, have a significant impact. This is caused by the high demand for banking services, whether for capital strengthening or fund storage, which has become an essential part of daily life. This study aims to analyze the role and contribution of Islamic banking to Indonesia's economy through a historical perspective. Using a descriptive qualitative method, the research examines the development of Islamic banking since the establishment of Bank Muamalat in 1992 to the present. The findings reveal that Islamic banking makes an important contribution in supporting the national economy, particularly through Sharia-based financing focused on empowering micro, small, and medium enterprises (MSMEs). However, Islamic banking faces significant challenges, such as low Islamic financial literacy, limited product innovation, and competition with conventional banking. To address these obstacles, strategic measures are required, including strengthening regulations, enhancing Islamic financial literacy education, and leveraging digital technology to expand access to financial services. These findings emphasize that collaboration among the government, society, and industry players is essential to strengthen the role of Islamic banking as a driver of equitable and sustainable economic growth.